Nexus between postpartum depression and exclusive breastfeeding practices among lactating mothers in Assosa Town, West Ethiopia - Abdurehim, Abdulfeta; Melaku, Yabsra; Hassen, Habtamu; Mosa, Hassen; Jemal, Musa; Abawari, Mohammed Jemal; Kemal, Abdurezak; Mohammed, Tofik; Biru, Bayise; Alemu, Emana; Ali, Anwar Seid; Mohammed, Bekri; et al. (Frontiers in Nutrition, 2024)
Background: postpartum depression (PPD) emerges as a notable public health issue, adversely affecting both Exclusive Breastfeeding (EBF) practices for infants and the fulfillment of parenting roles. Despite the lack of substantial evidence in Ethiopia, indicating the association between PPD and EBF practices, this study endeavors to fill this gap. The primary objective is to examine the correlation between PPD and EBF practices, along with exploring other pertinent factors, in Assosa Town, West Ethiopia Methods: A community-based cross-sectional study was carried out from March 07 to April 05, 2019. The study involved the recruitment of 462 participants through a systematic random sampling method. To screen PPD, we used Edinburgh Postnatal Depression Scale (EPDS) tool. This tool, EPDS, was used solely as a screening tool and not for diagnostic purposes. Bivariate and multivariate logistic regression analyses were employed to assess the association between independent variables and the dependent variable. Statistical significance was acknowledged at p < 0.05.The overall prevalence of EBF practices was found to be 58.2% (95% CI: 51.4-65.7), while the prevalence of PPD was 18.7% (95% CI: 15.94-26.7). Among mothers without PPD, the prevalence of EBF practices was notably higher at 62.4% (95% CI: 55.9%-65.2%) compared to mothers experiencing PPD, where the prevalence was 31.3% (95% CI: 24.7%-32.5%). Mothers who experienced PPD exhibited a 51% reduced odds of practicing EBF compared to their counterparts (AOR=0.49. 95% CI: 0.25-0.8). Furthermore, factors such as having a higher family monthly income (AOR=8.7, 95% CI: 4.2-17.2), being multiparous (AOR=5.8, 95% CI 4.9-10.8), attending antenatal care visits (AOR=4.9, 95% CI: 3.4-14.1), opting for vaginal delivery (AOR=9.8, 95% CI: 5.6-17.4), and receiving husband's support (AOR=5.3, 95% CI: 4.6-12.7) demonstrated a statistically significant positive association with EBF practices.In this study, a substantial number of mothers demonstrated suboptimal EBF practices during the first six months of their infants' lives. Consequently, the findings underscore a clear association between PPD and EBF. Thus, it is imperative to intensify efforts in early detection and treatment of PPD, enhance household income, advocate for antenatal care, and encourage active husband involvement to bolster EBF practices.